(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Synthetic polymers play a significant role in a variety of industries, especially packaging. However, it has a negative impact on the environment and creates issues with trash disposal and consumption. As a result, there’s a trend toward replacing the polymer with a biodegradable polymer that goes through a procedure. This study includes information on consumption, biodegradation, commercialization dependability, and renewable energy generation. Microorganisms may break down biodegradable and compostable materials into water, carbon dioxide, mineral salts, and new biomass in a certain amount of time. The circumstances under which a biodegradable or compostable plastic item dissolves and how fast it degrades are very dependent on the environment under which it is discarded. Commercialized biodegradable polymers includes starch based plastic, bacteria’s based plastic, cellulose-based plastics, soy-based plastics, lignin-based plastics, & naturally made fibers reinforced plastic. The manufacture of the kind of the materials & it introductions to markets are crucial for environment.